Consumer perception towards buying Malaysia products: a case study among customers in Western Pahang / Nor Hafiza Mohd Azmi - Mohd Azmi, Nor Hafiza (2011)
„Buy Malaysia Product Campaign‟ was introduced by The Ministry of Domestic Trade, Co- operatives And Consumerism and has been around for 27 years since 1984 where the purpose of this campaign is to escalate the consumer demand towards Malaysia product in order to reduce domestic dependency towards imported goods and to accelerate economic growth in the country. The primary purpose of this study is to identify the main factors that influence consumer perception towards buying Malaysia products at Western Pahang and focused at three area which are Bentong, Raub, and Temerloh. The researcher had distributed 150 questionnaires and only 130 of questionnaires were returned by respondents. This research examines whether local producers, product quality, brand conceptualization and Country of Origin are influence the consumer perception towards buying Malaysia products. The data were analyzed using SPSS through reliability, frequencies, and correlation. Based on the findings, three out four factors are significant relationship which are local producer, product quality and brand conceptualization while Country-of Origin factor is not significant. The most important factor to influence customer perception towards buying Malaysia products is product quality